Ocean circulation and shelf processes in the Arctic Mediterranean traced by radiogenic neodymium isotopes, rare earth elements and stable oxygen isotopes - Laukert, Georgi (2017)
Disentangling the sources, distribution and mixing of water masses involved in the transport and transfer of heat and freshwater in the Arctic Mediterranean (i.e. the Arctic Ocean and the Nordic Seas, AM) is critical for the understanding of present and future hydrological changes in the high-latitude regions. This study refines the knowledge of water mass circulation in the AM and provides new insights into the processes occurring on the Arctic shelves and in high-latitude estuaries. A multi-proxy approach is used combining dissolved radiogenic Nd isotopes (εNd), rare earth elements (REEs) and stable oxygen isotopes (δ18O) together with standard hydrographic tracers. The sources, distribution and mixing of water masses that circulate in the AM and pass the Fram Strait are assessed through evaluation of dissolved εNd and REE, and δ18O data obtained from samples recovered in 2012, 2014 and 2015, and through a compilation and reassessment of literature Nd isotope and concentration data previously reported for other sites within the AM. The Nd isotope and REE distribution in the central Fram Strait and the open AM is shown to primarily reflect the lateral advection of water masses and their mixing, whereas seawater-particle interactions exert important control only above the shelf regions. New insights into the processes occurring in high latitude estuaries are provided by dissolved Nd isotope and REE compositions together with δ18O data for the Laptev Sea based on filtered samples recovered in 2012, 2013 and 2014. A combination of REE removal through coagulation of nanoparticles and colloids and REE redistribution within the water column through formation and melting of sea ice and river ice is suggested to account for the distribution of all REEs, while no REE release from particles is observed. The ice-related processes contribute to the redistribution of other elements and ultimately may also affect primary productivity in high latitude estuaries. Die Bestimmung der Herkunft, Verteilung und Mischung von ...